Internet gaming disorder and risky behaviours among Czech adolescents: A nationally representative study - Suchá, Jaroslava; Dolejš, Martin; Dostál, Daniel; Pipová, Helena; Pontes, Halley M (Journal of behavioral addictions, 2024)
BACKGROUND AND AIMS: The aim of the present study was to estimate the complex association between Internet Gaming Disorder (IGD), substance use, and other risky behaviours in Czech adolescents whilst providing prevalence estimates of IGD and psychometric information regarding the Czech Internet Gaming Disorder Scale-Short-Form (IGDS9-SF). METHODS: A representative sample of 3,950 Czech adolescents was recruited through stratified random sampling in the school setting. RESULTS: Disordered gamers showed frequent use of specific substances such as pharmaceuticals, methylenedioxymethamphetamine, and lysergic acid diethylamide. In contrast, non-gamers had higher prevalence of alcohol, cigarettes, sedatives and tranquillisers, and marijuana use. A logistic regression, utilising IGDS9-SF raw scores and average daily gaming time, revealed a U-shaped relationship between gaming and both alcohol and cigarette use. Additionally, conduct problems such as bullying, and risky in-game behaviours were more prevalent among disordered gamers, with the exception of forging parents' signatures. The overall prevalence of IGD was 3.62% (95% CI = [3.1%, 4.3%]), with higher rates in males (5.89%; 95% CI = [4.9%, 7.0%]) than in females (1.45%; 95% CI = [1.0%, 2.1%]). DISCUSSION AND CONCLUSIONS: The Czech IGDS9-SF used in the present study showed adequate psychometric properties. The association between gaming and substance use behaviours may be specific and multifaceted depending on the severity of the gaming-related problems. Furthermore, disordered gamers may become more vulnerable due to a higher incidence of conduct problems, bullying (victimisation), and in-game risky behaviours such as engagement with microtransactions mechanics (e.g., loot box) within video games.
Keywords: riskování; Adolescent Behavior; Male; Internet Addiction Disorder; Adolescent; Česká republika; prevalence; netholismus; poruchy spojené s užíváním psychoaktivních látek; adolescence classification; substance use; mužské pohlaví; internet gaming disorder; mladiství; risky behaviour; Czech Republic; Risk-Taking; lidé; conduct problems; ženské pohlaví; Humans; Prevalence; Female; Substance-Related Disorders; chování mladistvých; videohry; Video Games